Outside of easy display of chronic obstructive pulmonary disease: clinical and functional-morphological aspects of changes of intestines - E. I. Beloborodova (Bûlleten' Sibirskoj Mediciny, 2009)
At patients chronic obstructive pulmonary disease (COPD) average degree of gravity and heavy stages decrease absorption functions of a thin gut is established concerning fats, protein, carbohydrates, progressing with weight of disease, a degree of degenerate-dystrophic changes of a mucous membrane of a thin gut with its infringement regeneration potentialities. The received data are interpreted in a context of interrelation of function, structure of a mucous thin gut and a clinical component. Direct correlation communications between deficiency of weight of a body of patients COPD and decrease absorption functions of a thin gut in the attitude are established albuminum (r = 0,71), fats (r = 0,55), carbohydrates (r = 0,48).